Development of a high-efficiency and wide-irradiation coil for transcranial magnetic stimulation therapy at home - Fushimi, M.; Kawasaki, Y.; Yamamoto, K.; Sekino, M. (AIP Advances, 2024)
To perform transcranial magnetic stimulation therapy at home, a stimulation coil that is robust against misalignment must be employed. A dome-shaped coil is one such coil; however, it has the disadvantage that the induced electric field is smaller than that of the conventional figure-8 coil. In this study, we developed a double D-shaped coil with a horizontal return path to suppress the influence of the return current, while reducing the inductance of the coil. After optimizing geometric parameters of the double D-shaped coil through numerical simulations, we fabricated the coil and evaluated its performance on healthy subjects. It was confirmed that the developed coil was found to tolerate a wider range of positioning errors than the figure-8 coil when stimulating the motor cortex.